Multi-protective effects of wheat embryo globulin on D-gal-induced aging mice - Aimei Liaoa; Xing Lyu; Jiarui Ma; Yinchen Hou; Ming Hui; Na Liu; Yi Zhao; Yixiang Cui; Jihong Huang (Food Science and Human Wellness)
Wheat embryo globulin (WEG) has been proven to possess multiple biological activities, including antioxidative properties, immunomodulatory, and so on. Aged mouse model were established by subcutaneous injection of D-galactose (D-gal), and the effects of WEG on learning, memory, and antioxidant capacity in aging mice were explored through behavioural tests and antioxidant enzyme activities determination. Compared with the Model group, WEG improved the percentage of the platform quadrant, increased the number of crossing platforms, and enhanced the identification indexs. WEG also increased total antioxidant capacity (T-AOC), superoxide dismutase (SOD), and glutathione peroxidase (GSH-Px) activities in the liver and brains of aging mice, and reduced malondialdehyde (MDA) content. Pathological observations indicated that WEG protected against damage to brain in D-gal-induced aging mice. These results effectively revealed that WEG not only improved the abilities of learning and memory, and the cognitive impairment, but also delayed the aging process of the D-gal-induced mice.